Articulation with primary attention to health care in the perspective of emergency service managers - Roberta Mendes Von Randow; Maria José Menezes Brito; Kênia Lara Silva; Angélica Mônica Andrade; Beatriz Santana Caçador; Andréia Guerra Siman (Rev Rene)
This is a qualitative case study which aimed at analysing the point of view of the Managers of Emergency Units (UPAs) concerning their association with the Primary Healthcare System. The subjects consisted of twenty-four managers of eight Emergency Units in Belo Horizonte-Brazil. Data was collected through semi-structured interviews from February to May 2011. The results indicate that the Emergency Units are perceived as the healthcare system observatory. For the articulation between the UPAs and APS the participants evidence as challenges the structural conditions of the APS healthcare system structure, difficulties in the healthcare system management and organization, and healthcare conceptions prevalent in the society. Among the possibilities of articulation we may highlight the on-going agreements and the acknowledgment of complementarity and interdependence among different services.